The Effect of Earthquake Simulation Animation Videos on The Knowledge And Skills of Earthquake Disaster Preparedness in The 5th-Grade Elementary School Klatak Banyuwangi 2023 - Masroni Masroni; Andrik Hermanto; Hillary Elsafitra (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2024)
Introduction: Disaster preparedness involves preparing a counter-disaster plan, warning of the disaster, and maintaining resources needed during and after a disaster. The media that can be used by using animated videos can increase knowledge and skills more easily and interestingly for elementary school students. Objectives: This study aimed to investigate the effect of earthquake simulation animation videos on the knowledge and skills of earthquake disaster preparedness in the 5th-grade Elementary School Klatak Banyuwangi. Methods: This study used a pre-experimental research plan with a one-group pre-test post-test research design of 56 respondents with a total sampling technique. Then, statistical analysis was done using the Wilcoxon Signed Rank Test from SPSS 16. Results: Before being given an animated video, they had a knowledge level of scores, most of them as much as 41% in the category of unprepared, mostly 62.5% competent enough for skills. After being given an animated video, knowledge increased to 64.3% with ready criteria, and skills increased to 82.1% with very competent criteria. With a significance value of p=0.000<0.05, there was a significant Effect of Earthquake Simulation Animation Videos on the Knowledge and Skills of Earthquake Disaster Preparedness in 5th grade elementary School Klatak Banyuwangi 2023. Conclusions: Applying knowledge and skills in earthquake disaster preparedness can be done early, starting from elementary school, one of which is by using animated video media, which is expected to be more easily understood, interesting, and can be applied in everyday life.